1975
DOI: 10.1113/jphysiol.1975.sp010861
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sodium salicylate on bile secretion in the dog.

Abstract: SUMMARY1. The i.v. injection of sodium salicylate (100 mg/kg) in the dog caused a rapid and maintained choleresis of the order of 300-600% of control levels.2. The total amount of salicylate excreted in bile was only 1-2 % of that injected.3. The secretion of bile salt into bile was not increased by salicylate. 4. The choleresis caused by salicylate was associated with a decrease in the concentrations of sodium and of bile salt in bile, and with an increase in the concentration of chloride; the biliary concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A choleretic effect of sodium salicylate has been reported by Rutishauser & Stone (1973). In the present work it has been shown that a marked increase in bile flow can also be produced by acetylsalicylate, when administered intravenously as the water-soluble lysine derivative.…”
Section: Discussionmentioning
confidence: 73%
“…A choleretic effect of sodium salicylate has been reported by Rutishauser & Stone (1973). In the present work it has been shown that a marked increase in bile flow can also be produced by acetylsalicylate, when administered intravenously as the water-soluble lysine derivative.…”
Section: Discussionmentioning
confidence: 73%
“…They [4] also reported first and second cmc values of mixtures of sodium dodecyl sulfate with various bile salts as these mixtures formed mixed micelles. The secretion of bile by the liver into the gallbladder is called choleresis and salicylate ion is known to have a choleretic effect in rats, dogs, and humans [5][6][7][8]. Choleretic effect refers to increasing the rate of bile flow and the mechanism by which salicylate exhibits this effect is not clearly known.…”
Section: Introductionmentioning
confidence: 98%
“…Choleretic effect refers to increasing the rate of bile flow and the mechanism by which salicylate exhibits this effect is not clearly known. It is reported [5] that the influence of salicylate anion on the bile salt micelles might be one of the reasons for its choleretic effect. Further, there are reports of bile salts affecting the colonic absorption of oxalate and inhibition of calcium oxalate precipitation by bile salts [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Infusion of sodium salicylate (SA) or lysine acetylsalicylate (ASA) increased bile flow in dogs and monkeys (17)(18)(19). Bile salt secretion did not change in dogs given the salicylates (17,19), but lecithin and cholesterol secretion fell markedly in those given lysine ASA (19). Bile lipid secretion was not altered in monkeys infused with sodium SA (18).…”
mentioning
confidence: 99%